Telecentre Replication Initiative In Borneo Malaysia: The Coeri Experience - Wee, Alvin Yeo; Faisal S., Hazis; Tariq, Zaman; Peter, Songan; Khairuddin, Ab Hamid (EJISDC, 2011)
There are many bridging-the-digital-divide initiatives implemented by various government agencies and non-governmental organisations throughout the world. Numerous studies have been conducted to identify the critical success factors in providing remote and rural communities equitable access to Information and Communication Technologies (ICTs). Malaysia has its fair share of successes and failures in such initiatives. One such initiative, the eBario Project, which provided ICTs to the rural and remote community in Bario, Borneo Malaysia, has been in operation over the last decade. The project was undertaken by the Centre of Excellence for Rural Informatics (CoERI), Institute of Social Informatics and Technological Innovations, Universiti Malaysia Sarawak (UNIMAS) with active participation of the local community in Bario. Critical success factors of the eBario Project include the close cooperation between the project initiator and the local community, strong support from the local champions, focus on actual needs and socio-economic goals of the community, and deployment of appropriate technologies to the remote community. Given its relative success, the eBario project has been replicated to four other rural and remote communities in Borneo Malaysia. This paper highlights the approach used in implementing telecentres within these communities and some of the lessons learnt during the replication process. The CoERI Experience provides a useful guide to policy makers, project implementers and researchers who intend to deploy telecentres in rural communities at a larger scale.